Effect of Functional Training on Physical Fitness Among Athletes: A Systematic Review - Xiao, Wensheng; Soh, Kim Geok; Wazir, Mohd Rozilee Wazir Norjali; Talib, Othman; Bai, Xiaorong; Bu, Te; Sun, He; Popovic, Stevo; Masanovic, Bojan; Gardasevic, Jovan (Frontiers in Physiology, 2021)
There is growing empirical evidence that functional training is beneficial for the overall physical fitness of athletes. In recent years, functional training has been incorporated in exercise training programs to improve physical fitness among athletes. However, there is a lack of a systematic review focused on the effects of functional training on athletes’ physical fitness. Thus, the aim of the present review is to clarify the effects of functional training on physical fitness among athletes. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes guidelines, the systematic search of PubMed, SCOPUS, EBSCOhost, and CINAHL Plus databases was undertaken in August 2020 to identify the repotted studies, using a combination of keywords related to functional training, physical fitness, athletes. From a pool of 145 studies, only nine articles met all eligibility criteria and were included in the systematic review. The quality of the study included in the 9 studies is fair (ranged from 3-4). The results showed that speed (n=6) was the major criterion studied in functional training interventions, followed by muscular strength (n=5), power (n=4), balance (n=3), body composition (n=3), agility (n=3), flexibility (n=1) and muscular endurance (n=1). Existing evidence concludes that functional training significantly impacts speed, muscular strength, power, balance, and agility. Furthermore, there is moderate evidence of the effect of functional training on flexibility and muscular endurance. In contrast, no significant improvement was found in body composition where functional training was conducted.